The Neoproterozoic basement of the Sauce Chico Inlier (Ventania System): Geochemistry and U–Pb geochronology of igneous rocks with African lineage in central-eastern Argentina - Ballivián Justiniano, Carlos A. (2020)
Fil: Ballivián Justiniano, Carlos. Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET). Instituto de Recursos Minerales (INREMI), Universidad Nacional de La Plata–Comisión de Investigaciones Científicas de la Provincia de Buenos Aires; Argentina.